Circulating cotinine concentrations and lung cancer risk in the Lung Cancer Cohort Consortium (LC3). (12th June 2018) - Larose, Tricia L; Guida, Florence; Fanidi, Anouar; Langhammer, Arnulf; Kveem, Kristian; Stevens, Victoria L; Jacobs, Eric J; Smith-Warner, Stephanie A; Giovannucci, Edward; Albanes, Demetrius; Weinstein, Stephanie J; Freedman, Neal D; et al.
Abstract: Background: Self-reported smoking is the principal measure used to assess lung cancer risk in epidemiological studies. We evaluated if circulating cotinine—a nicotine metabolite and biomarker of recent tobacco exposure—provides additional information on lung cancer risk. Methods: The study was conducted in the Lung Cancer Cohort Consortium (LC3) involving 20 prospective cohort studies. Pre-diagnostic serum cotinine concentrations were measured in one laboratory on 5364 lung cancer cases and 5364 individually matched controls. We used conditional logistic regression to evaluate the association between circulating cotinine and lung cancer, and assessed if cotinine provided additional risk-discriminative information compared with self-reported smoking (smoking status, smoking intensity, smoking duration), using receiver-operating characteristic (ROC) curve analysis. Results: We observed a strong positive association between cotinine and lung cancer risk for current smokers [odds ratio (OR ) per 500 nmol/L increase in cotinine (OR500 ): 1.39, 95% confidence interval (CI): 1.32–1.47]. Cotinine concentrations consistent with active smoking (≥115 nmol/L) were common in former smokers (cases: 14.6%; controls: 9.2%) and rare in never smokers (cases: 2.7%; controls: 0.8%). Former and never smokers with cotinine concentrations indicative of active smoking (≥115 nmol/L) also showed increased lung cancer risk. For current smokers, the risk-discriminative performance of cotinine combined with self-reported smoking (AUCintegrated : 0.69, 95% CI: 0.68–0.71) yielded a small improvement over self-reported smoking alone (AUCsmoke : 0.66, 95% CI: 0.64–0.68) ( P = 1.5x10 –9 ). Conclusions: Circulating cotinine concentrations are consistently associated with lung cancer risk for current smokers and provide additional risk-discriminative information compared with self-report smoking alone.